Psychotropic Substances 2016 - International Narcotics Control Board (United Nations, 2017)
This annual publication produced by the United Nations Office on Drugs and Crime provides up-to-date and comprehensive statistics as well as assessments of annual medical and scientific requirements concerning psychotropic substances; the various levels of consumption of groups of the substances, and also the prohibitions and restrictions relative to their export and import. This trilingual publication contains the English, French and Spanish versions.